Pedagogical translanguaging in Content and Language Integrated Learning. - Cenoz, Jasone; Gorter, Durk (Journal of Multilingual Theories & Practices, 2022)
Translanguaging has its origin in Welsh bilingual education and it refers to a pedagogical practice which alternates the languages of the input and the output in the same lesson. Pedagogical translanguaging is closely related to the original approach to translanguaging but goes beyond the practice of language alternation. Pedagogical translanguaging is learner-centred and endorses the development of all the languages used by learners. It fosters the development of metalinguistic awareness and goes against the tradition of language separation in school settings by softening boundaries between languages when learning languages and content. This article discusses the challenge of using pedagogical translanguaging in Content and Language Integrated Learning (CLIL). CLIL programmes are more demanding than regular programmes because content is taught through the medium of a second or additional language. The language used in content subjects is in many cases substantially different and more complex than the language used in language classes. Pedagogical translanguaging can support students in CLIL programmes when working with new concepts and academic uses of the language, and can be adapted to synchronous and asynchronous online learning.